PEMANFAATAN MEDIA CANVA DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) PADA PEMBELAJARAN IPAS DI SD - Azizah, Nida Nur; Fathurrahman, Moh. (Universitas Negeri Medan, 2024)
Abstract: The purpose of this study is to ascertain how the use of Canva media in conjunction with a Culturally Responsive Teaching (CRT) strategy affects student learning results in science classes V and science topics at SDN Sawojajar 01. Teachers have a problem when creating learning materials that meet the requirements of students from a variety of backgrounds. In this study, a nonequivalent control group design is employed in conjunction with a quasi-experimental quantitative technique. Pretest-posttest multiple choice questions are used in the study instrument. It was shown that (0.00<0.05) based on the findings of the hypothesis test, which was conducted using the t-test. In light of this, it may be said that integrating Canva media into a culturally sensitive teaching strategy can enhance primary school scientific learning objectives.Keyword: Media, Canva, Culturally Responsive Teaching (CRT), Learning OutcomeAbstrak: Penelitian ini bertujuan untuk mengetahui hasil belajar siswa pada mata pelajaran IPAS kelas V SDN Sawojajar 01 yang dipengaruhi oleh penggunaan media Canva dengan pendekatan Culturally Responsive Teaching (CRT). Latarbelakang siswa yang beragam menjadi tantangan bagi guru dalam merancang media pembelajaran yang sesuai dengan kebutuhan. Penelitian ini menggunakan metode kuantitatif eksperimen semu (quasi eksperimental design) dengan desain nonequivalent control group design. Instrumen penelitian menggunakan soal pilihan ganda pretest-posttest. Berdasarkan hasil uji hipotesis yang telah dilakukan menggunaka uji-t menunjukkan (0,00<0,05). Sehingga dapat disimpulkan penggunaan media canva dengan pendekatan culturally responsive teaching dapat meningkatkan hasil belajar IPAS di SD.Kata Kunci: Media, Canva, Culturally Responsive Teaching (CRT), Hasil Belajar